2023
DOI: 10.1177/17588359231156669
|View full text |Cite
|
Sign up to set email alerts
|

The association between HER2-low expression and prognosis of breast cancer: a systematic review and meta-analysis

Abstract: Background: The use of antibody–drug conjugates for the treatment of advanced-stage human epidermal growth factor receptor 2 (HER2)-low expression in breast cancer (BC) has shown prominent curative effects, which has led to increased academic interest. However, the role of HER2-low expression in the prognosis of BC remains controversial. Methods: We conducted a systematic search of the PubMed, Embase, and Cochrane library databases and several oncology conferences until 20 September 2022. We used fixed- and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…Some studies found no survival differences comparing patients with ERBB2-low tumors with patients with ERBB2-negative tumors, while others found ERBB2-low to be significant in RFS, BCSM, and OS . However, in several meta-analyses, significant differences were present in clinical outcomes between ERBB2-low and ERBB2-negative tumors . We found significant OS benefit associated with ERBB2-low compared with ERBB2-negative in the hormone receptor–negative BC group (ie, TNBC).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Some studies found no survival differences comparing patients with ERBB2-low tumors with patients with ERBB2-negative tumors, while others found ERBB2-low to be significant in RFS, BCSM, and OS . However, in several meta-analyses, significant differences were present in clinical outcomes between ERBB2-low and ERBB2-negative tumors . We found significant OS benefit associated with ERBB2-low compared with ERBB2-negative in the hormone receptor–negative BC group (ie, TNBC).…”
Section: Discussioncontrasting
confidence: 46%
“…[23][24][25][26][27][28][29] However, in several meta-analyses, significant differences were present in clinical outcomes between ERBB2-low and ERBB2-negative tumors. [30][31][32][33][34][35] We found significant OS benefit associated with ERBB2-low compared with ERBB2-negative in the hormone receptor-negative BC group (ie, TNBC). We also evaluated the significance of TILs in all subgroups and found that for every 10% increase in TILs, there was a significant increase in the RFS and BCSM in the hormone receptor-negative and ERBB2-low group but not in any other groups, including the hormone receptor-negative and ERBB2-negative group.…”
Section: Jama Network Open | Oncologymentioning
confidence: 74%
“…Furthermore, the HER2-low group less frequently had unfavorable risk factors. Lastly, Tang et al analyzed 15 and 9 studies with OS and DFS data and found similar results, including lower pCR rates (HR=0.98, 95% CI=0.96-0.99; p=0.001; and HR=0.96, 95% CI=0.94-0.99; p=0.003) (46).…”
Section: Discussionmentioning
confidence: 75%
“…Several recently published systematic reviews and meta-analyses investigated the prognostic significance of HER2-low compared to HER2-zero in early breast cancer ( Table 1 ) [ 13 17 ]. A HER2-low status was associated with a better OS in all but one meta-analysis.…”
mentioning
confidence: 99%
“…A HER2-low status was associated with a better OS in all but one meta-analysis. That analysis found no significant association between HER2-low and DFS in the overall population but only in the HR-positive subgroup (HR 0.96, 95% CI 0.94–0.99, P = 0.003) [ 17 ]. In fact, others have confirmed that the association of a HER2-low status with survival is strongest in HR-positive carcinomas [ 15 ].…”
mentioning
confidence: 99%